TINGKAT PERUBAHAN KESEJAHTERAAN EKONOMI KELUARGA BURUH MIGRAN - Rohmah, Babun Ni’matur; Purnama Sari, Riska Ayu (LP3M IAI Al-Qolam, 2017)
Gondanglegi sub district is occupying the first position as the largest supplier of migrant workers in the area of Ã¢â¬â¹Ã¢â¬â¹South Malang in 2014. This research focuses on Panggungrejo Village as the object of research. A village with area of Ã¢â¬â¹Ã¢â¬â¹203 km2, population of 1,877 people consisting of 866 men and 1,011 women. This village pervades 12 RTs, and this research took 2 RTs namely RT 5 and 6, with 5 respondents. These five respondents are representatives of various migrant workers. Some represent their wives as migrant workers, husbands and children. This study uses the theory of social mobility; a change, shift, increase or decrease of the status and role of its members. Welfare indicators used are economic, educational, social and health. The result of the research shows that there is a change of the respondentsÃ¢â¬â¢ life level in terms of economic, social, educational and even health compared to prior becoming migrant worker, although the rate of change is not too significant. Keywords: Welfare, Migrant Worker, Social Mobility.